The handbook of phonological theory - Goldsmith, John A., 1951-; Riggle, Jason; Yu, Alan C. L. (Chichester, West Sussex, UK ; Malden, MA : Wiley-Blackwell, 2011)
" ... an innovative and detailed examination of recent developments in phonology. Revised from the ground up, the book is comprised almost entirely of newly-written and previously unpublished chapters. Offers new and unique contributions reflecting the advances in phonological theory since publication of the first edition in 1995 -- Addresses the important questions in the field including learnability, phonological interfaces, tone, and variation, and assesses the findings and accomplishments in these domains -- Features contributions by an international team of leading phonologists."--Provided by publisher.
ch. 1. Rules v. constraints -- ch. 2. Opacity and ordering -- ch. 3. The Interaction between morphology and phonology -- ch. 4. Quantity -- ch. 5. Stress systems -- ch. 6. The syllable -- ch. 7. Tone : is it different? -- ch. 8. Harmony systems -- ch. 9. Contrast reduction -- ch. 10. Diachronic explanations of sound patterns -- ch. 11. Phonetics in phonology -- ch. 12. Corpora and exemplars in phonology -- ch. 13. The place of variation in phonological theory -- ch. 14. The syntax-phonology interface -- ch. 15. Intonation -- ch. 16. Dependency-based phonologies -- ch. 17. The acquisition of phonology -- ch. 18. Phonology as computation -- ch. 19. Using psychological realism to advance phonological theory -- ch. 20. Learning and learnability in phonology -- ch. 21. Sign language phonology -- ch. 22. Language games -- ch. 23. Loanword adaptation : from lessons learned to findings.
Includes bibliographical references and index.
Print version record.
Keywords: Grammar, Comparative and general -- Phonology; Cognitive grammar; Functionalism (Linguistics); Grammar, Comparative and general -- Phonology; Tone (Phonetics); LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Phonetics & Phonology; Grammar, Comparative and general -- Phonology; Phonologie; Electronic books